2012
DOI: 10.1371/journal.pone.0044922
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Cramps and Neuropathies in Patients with Allogeneic Hematopoietic Stem Cell Transplantation and Graft-versus-Host Disease

Abstract: ObjectiveGraft-versus-host disease (GVHD) is an immune-mediated multisystemic disorder and the leading cause of morbidity after allogeneic hematopoietic stem cell transplantation. Peripheral nervous system manifestations of GVHD are rare but often disabling. Whereas immune-mediated neuropathies are an established feature of GVHD, muscle cramps are not well characterized.MethodsIn a single-centre retrospective cohort we studied 27 patients (age 23 to 69 years) with GVHD (acute n = 6, chronic n = 21) who complai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
(56 reference statements)
3
19
0
1
Order By: Relevance
“…Finally, peripheral nervous system involvement in course of chronic graft‐versus‐host disease (cGvHD), a major side effect of allogeneic hematopoietic stem cell transplantation, a procedure most often applied in heavily pre‐treated relapsed lymphoma patients, should be mentioned. It may present with different clinical manifestations, among which cramps, large and small fibers polyneuropathy of different degree of severity and impact on the quality of life . A recent prospective study on 27 patients with cGvHD reported that almost all (92.6%) the patients developed peripheral neuropathy, 6% with mixed large and small fibers neuropathies, the latter associated with pain.…”
Section: Chemotherapy‐induced Neurotoxicitymentioning
confidence: 99%
“…Finally, peripheral nervous system involvement in course of chronic graft‐versus‐host disease (cGvHD), a major side effect of allogeneic hematopoietic stem cell transplantation, a procedure most often applied in heavily pre‐treated relapsed lymphoma patients, should be mentioned. It may present with different clinical manifestations, among which cramps, large and small fibers polyneuropathy of different degree of severity and impact on the quality of life . A recent prospective study on 27 patients with cGvHD reported that almost all (92.6%) the patients developed peripheral neuropathy, 6% with mixed large and small fibers neuropathies, the latter associated with pain.…”
Section: Chemotherapy‐induced Neurotoxicitymentioning
confidence: 99%
“…Insomnia is also a common side effects of taking corticosteroids particularly if the medication taken closer to bedtime. Muscle cramps and neuropathy have been found to be common among patients with GVHD and to disrupt sleep (41); neuropathy is also a risk factor for RLS (42). These factors and others can also perpetuate existing sleep problems and contribute to the development of persistent (lasting more than 3 months) or recurrent sleep problems.…”
Section: Sleep Disruption and Disorders Following The Acute Transplanmentioning
confidence: 99%
“…This case illustrates that cGVHD is not only associated with muscle cramps and polyneuropathies but can also cause peripheral nerve entrapment syndromes. The patient had long‐standing cGVHD affecting multiple organs, including fascia.…”
Section: Discussionmentioning
confidence: 91%
“…Chronic GVHD (cGVHD) can involve the peripheral nervous system and usually starts several months to years after allo‐HSCT . The clinical and electrophysiological presentation of cGVHD‐associated acute and chronic neuropathies is heterogeneous and can resemble Guillain–Barré syndrome, chronic inflammatory demyelinating polyneuropathy, or chronic immune‐mediated axonal polyneuropathy . Although cGVHD is often associated with dermal and fascial sclerosis, entrapment neuropathies have not been described.…”
mentioning
confidence: 99%